1980
DOI: 10.1007/bf01477733
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous recording of monophasic action potentials and contractile force from the human heart

Abstract: Cardiac monophasic action potentials (MAPs) and contractility have been simultaneously measured in man while the heart rate was being changed by right atrial pacing. A new non-suction electrode was used for safe and long-term recording of MAPs from the endomyocardium. Abrupt changes in cycle-length were followed first by a fast, then a slow response in the adaptation of MAP-duration and of contractility (LV dp/dt max) to the new steady state. After increasing the heart rate then slow phase of MAP shortening ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…Slow changes in a.p.d., similar to those reported here, have been observed in many other cardiac tissues (Boyett & Jewell, 1980) including human ventricular muscle (Franz, Sch6ttler, Schaefer & Seed, 1980). Boyett & Jewell (1978), for example, showed that when cat ventricular muscle is rested the action potential becomes progressively longer over a time course lasting several hundred seconds; this is similar to the behaviour exhibited by dog Purkinje fibres, and it is therefore possible that rate-dependent changes in Na-K-pump activity influence the duration of the action potential in other tissues.…”
Section: Incomplete Recovery Of the Plateau Conductancessupporting
confidence: 85%
“…Slow changes in a.p.d., similar to those reported here, have been observed in many other cardiac tissues (Boyett & Jewell, 1980) including human ventricular muscle (Franz, Sch6ttler, Schaefer & Seed, 1980). Boyett & Jewell (1978), for example, showed that when cat ventricular muscle is rested the action potential becomes progressively longer over a time course lasting several hundred seconds; this is similar to the behaviour exhibited by dog Purkinje fibres, and it is therefore possible that rate-dependent changes in Na-K-pump activity influence the duration of the action potential in other tissues.…”
Section: Incomplete Recovery Of the Plateau Conductancessupporting
confidence: 85%
“…MAPS were recorded using a modification of a newly designed contact-electrode recording technique (13). The electrophysiological principle underlying this technique is described elsewhere (16).…”
Section: Methodsmentioning
confidence: 99%
“…While a close relationship between action potential duration and the resulting contractile force was documented decades ago [25], the dependence of atrial cell shortening on the plateau potential is less well appreciated in the literature. In ventricular voltage clamped myocytes, cell shortening is paralleled by the bell-shaped current-voltage relationship of I CaL , with low contraction amplitude at positive potentials of N 40 mV [26,27].…”
Section: Modulation Of Atrial Contractility By the Shape Of The Atriamentioning
confidence: 99%